MANAGING HIV/AIDS WORKPLACE PROGRAMMES IN THE GAUTENG ARMY UNITS - KHULA, PULE ARTHUR (My University, 2013)
The Human Immunodeficiency Virus and Acquired Immune Deficiency Syndrome (HIV/AIDS) epidemic could be devastating if it is not effectively and efficiently managed. Its negative impact on the military could make that country vulnerable to any form of attack since the military is the first and last line of defence in any country. The unavailability of HIV Prevalence Rates in the South African National Defence Force (SANDF), and low voluntary counselling and testing (VCT) uptake in its ranks should be worrying. The low VCT uptake is directly linked to the management of HIV/AIDS Workplace programmes at the military unit level, while the absence of HIV prevalence rates is attributable to the sensitive way military organizations in general perceive the publication of HIV prevalence rates of their members. The unavailability of HIV Prevalence Rates in the SANDF is not directly attributable to the lack of effective and efficient management of HIV/AIDS workplace programmes, but is due to the general attitude that permeates most militaries in the world of refusing to make public HIV Prevalence Rates by military leadership. Most military leaders, including the SANDF, consider HIV Prevalence Rates to be sensitive and therefore should be kept secret. The low VCT uptake in the military units is due to an incomprehensible HIV/AIDS policy, non-existence HIV/AIDS Workplace programme, lack of leadership, stigma and discrimination, and lack of monitoring and evaluation. It is in this context that the Lenasia Military Base and military units need to establish an effective and efficient integrated HIV/AIDS workplace programme.
MM (P&DM) thesis
Keywords: HIV/AIDS in the workplace